Bridging the gap between clinical trials and community care: Translating a memory group for older people with mild cognitive impairment into a community‐based organisation. (18th September 2019) - Kinsella, Glynda J.; Mullaly, Elizabeth; Rand, Elizabeth; Pike, Kerryn E.; Reilly, Ann; Cavuoto, Marina G.
Abstract: Objectives: Older people with mild cognitive impairment (MCI) are seeking interventions for maintaining independence. This study investigates the feasibility of translating a research‐evaluated memory group (LaTCH) into a community‐based organisation by evaluating the experiences of clients and trained staff. Methods: Dementia Australia staff trained as facilitators of memory groups for 274 people with MCI and families. Clients and staff were interviewed regarding experiences from group participation. Results: Clients and staff reported benefits of shared experience through group participation, leading to greater use of compensatory strategies. Staff observed client improvement in memory‐related self‐confidence, thereby reducing anxiety and increasing re‐engagement in life activities. In their own professional roles, staff reported increased self‐efficacy, leading to greater role satisfaction. Several challenges in running and sustaining the program were also identified. Conclusions: Memory group interventions can be feasibly delivered in a community setting and increase service access opportunities for older people with memory problems.